Attention test D2: Normative data and attention development in elementary grades (European Journal of Education and Psychology, 2012)
The main purpose of this study has been to analyze the attention development in children of elementary grades and to obtain standardization of the test d2. A sample of 1.032 was selected 1 st to 6 th grade belonging to schools in the Canary Islands with an age range between 6 years and 3 months old to 12 years and 4 months old. We analyzed changes observed over the years in all variables measured by Test d2. The results found reveal the existence of significant changes in the productivity variables and effectiveness but not in the measure of errors. Furthermore, the percentiles were calculated for each of the measures of d2 for each age range.